Thyroglobulin measurements in fine‐needle aspiration cytology of lymph nodes for the detection of metastatic papillary thyroid carcinoma. Issue 8 (12th March 2013) - Li, Qing Kay; Nugent, Summer L.; Straseski, Joely; Cooper, David; Riedel, Stefan; Askin, Frederic B.; Sokoll, Lori J.
<x xml:space="preserve">Abstract</x> BACKGROUND Ultrasound‐guided fine‐needle aspiration (US‐FNA) cytology is a commonly used method in the surveillance of suspicious lymph nodes (LNs) in patients with papillary thyroid carcinoma (PTC). The measurement of thyroglobulin (Tg) levels in LNs during FNA has been suggested to improve the diagnosis. In the current study, the use of US‐FNA‐Tg in LNs that were suspicious for metastatic PTC was investigated. METHODS A total of 208 cases from the Johns Hopkins Hospital with both US‐guided FNA cytology and US‐FNA‐Tg measurements were included; 60 cases had follow‐up surgeries performed. Tg levels were correlated with cytological and histological diagnoses. RESULTS Of 35 cases of cytologically diagnosed metastatic PTC, 34 were confirmed by surgery. The median US‐FNA‐Tg concentration was 4232.7 ng/mL, whereas in 112 benign LNs the median Tg concentration was < 0.2 ng/mL (P < .0001). Receiver operating characteristic analysis (area under the curve, 0.949) demonstrated a sensitivity of 97% and a specificity of 81% at the Tg detection limit (<0.2 ng/mL), whereas cutoff values of 9.6 ng/mL to 100 ng/mL resulted in a sensitivity of 76% and a specificity of 98%. Of 15 cases with a cytological diagnosis of "suspicious for PTC, " 9 cases had markedly elevated Tg levels detected on FNA. Seven of these 9 cases had follow‐up surgeries confirming the diagnosis of PTC. Of 29 cases with a "nondiagnostic" cytology, 7 had markedly elevated Tg levels on FNA, with a median of 1305.5 ng/mL, and were confirmed to be metastatic PTC at surgery. CONCLUSIONS US‐FNA‐Tg demonstrated a strong negative predictive value (93%‐99%). It may be particularly useful for difficult cases. However, standardization of the sample collection is still needed to further improve the accuracy of the approach. Cancer (Cancer Cytopathol) 2013;121:440‐8. © 2013 American Cancer Society.